TaraLetsFly.com proposed business plan for an online travel agency with a search engine for flights offered by Local Airlines - Ignacio, Charity M. (University of the Philippines Diliman, 2012)
This is a business plan for TaraLetsFly.com. TaraLetsFly.com is conceptualized as an Online Travel Agency (OTA) with an online flight booking system available on its website. Local tourism has been improving in the country and the number of Filipinos engaging in travel has been increasing. The continuous expansion of the online community is also noticeable with the growing population of Filipinos on Facebook, frequency of online seat sales popularized by Cebu Pacific and the number of online promo sites (such as Groupon Ph, Deal Grocer, Cash Cash Pinoy and Ensogo) with local offerings including some travel packages. With this growth, it is apparent that the confidence on online transactions has also been increasing. For those who book their flights online, one of the difficulties for consumers is to search through different airline websites for the best flight schedule at the best prices. TaraLetsFly.com leverages on making an online flight booking facility that consolidate flight search. While there are several sites that offer such service for international flights, to date, there is no local version of this designed for consumers. At best, there is a website that offers this facility for travel agents only. This is a niche that can be explored, targeting online Filipino and foreign travelers and tourists going to and from the Philippines, and planning their inter-island travels with the Philippines. Literature review was done for four main topics : business plan, business models, first-mover advantage and barriers to entry. From the literature review, the structure of the business plan was derived. It also shows the different kinds of business models and how the business model can be used as the foundation for building the business plan. It is also discussed the sources of first mover advantages and the potential barriers to entry. The methodologies used for the strategic market research, projections and financial research as well as their limitations are discussed in this business plan. For the strategic market research, an online survey is conducted to learn more about the target market. An interview was also done with some airline representatives as well as with an IT practitioner who is also an owner of a travel agency. For the projections, the sources of data and trends are identified. It is also discussed how Linear Regression is used for these projections. For the financial research, the companies whose financial statements were used as models for the financial estimates are identified and the reasons for choosing these companies are discussed. The assumptions for the computations are also discussed. The business model is the main foundation of this business plan, thus, the business model of TaraLetsFly.com is discussed in detail. Its vision and mission involve providing travel planning tools that will help travelers and tourists as well as the travel industry. Osterwalder's Business Model Canvas is used to design this business plan for TaraLetsFly.com illustrating the relationships among customer segments, value proposition, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. For financial analysis, capital spending and fund requirement are estimated that amounted to 4 million pesos. Profit potential is shown from the apparent growth in air travel and growing revenues of airlines. Projected earnings from commission and discounts as well as advertising are computed from 2014 to 2018. It is assumed that there will be no earning in 2013 because this year is allotted for development. Although, the venture is already expected to have some revenue of around 13.7 million pesos in 2014, operational expenses, payment from loans, and such a conservative projection turn this revenue into net loss of over 85 thousand in its first year of operation. However, by 2015, it is expected to make around 3.4 million net income and it goes up to nearly 6 million net income and increasing its asset value to 16 million by 2018. These are reflected in the pro forma financial statements. Analysis of the factors of return on investment was also done that showed the venture's net present value, internal rate of return and profitability index of benefit/cost ratio at two different discount rates. The discount rates used are 10 percent and 50 percent. 10 percent is used for estimating the venture's value with only the inflation in mind. For the last decade, the inflation rate has not even reached 10 percent. 50 percent is computed for to take into consideration that a venture capitalist expects to see returns from their investment. All the assumptions for the computations are enumerated.